WHO, WHEN, HOW: a scoping review on flexible at-home respite for informal caregivers of older adults - Maude Viens; Alexandra Éthier; Véronique Provencher; Annie Carrier (BMC, 2024)
Abstract Background As the world population is aging, considerable efforts need to be put towards developing and maintaining evidenced-based care for older adults. Respite services are part of the selection of homecare offered to informal caregivers. Although current best practices around respite are rooted in person centeredness, there is no integrated synthesis of its flexible components. Such a synthesis could offer a better understanding of key characteristics of flexible respite and, as such, support its implementation and use. Methods To map the literature around the characteristics of flexible at-home respite for informal caregivers of older adults, a scoping study was conducted. Qualitative data from the review was analyzed using content analysis. The characterization of flexible at-home respite was built on three dimensions: WHO, WHEN and HOW. To triangulate the scoping results, an online questionnaire was distributed to homecare providers and informal caregivers of older adults. Results A total of 42 documents were included in the review. The questionnaire was completed by 105 participants. The results summarize the characteristics of flexible at-home respite found in the literature. Flexibility in respite can be understood through three dimensions: (1) WHO is tendering it, (2) WHEN it is tendered and (3) HOW it is tendered. Firstly, human resources (WHO) must be compatible with the homecare sector as well as being trained and qualified to offer respite to informal caregivers of older adults. Secondly, flexible respite includes considerations of time, duration, frequency, and predictability (WHEN). Lastly, flexible at-home respite exhibits approachability, appropriateness, affordability, availability, and acceptability (HOW). Overall, flexible at-home respite adjusts to the needs of the informal caregiver and care recipient in terms of WHO, WHEN, and HOW. Conclusion This review is a step towards a more precise definition of flexible at-home respite. Flexibility of homecare, in particular respite, must be considered when designing, implementing and evaluating services.